Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Cumulative Review: 32

Answer

Answer: $4x^{2}$ -1

Work Step by Step

(2x + 1)(2x - 1) This can be put in a generalized statement: (a + b)(a - b) = $a^{2} - b^{2}$. Comparing the statement wth our expression, a = 2x and b = 1. Thus, (2x + 1)(2x - 1) = $(2x)^{2} - 1^{2}$ = $4x^{2}$ -1.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.